Konsistensi Penyelenggaraan RRI dan TVRI sebagai Lembaga Penyiaran Publik - Atie Rachmiatie (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Broadcasting Act No. 32/2002 has transformed Radio Republik Indonesia (RRI) and Televisi Republik Indonesia (TVRI) from a state-owned-body to public-broadcasting-service. This research aimed to investigate the impacts experienced by those two organizations concerning their philosophies, role, functions, and its implementation on operational levels. Utilizing case studies in West Java and South Sulawesi (Makasar), it is found that broadcasting dynamics in both area are highly dynamic. On the level of normative, both are consistent enough. But on the level of empirical implementation, there were still many obstacles. Although institutional structure relatively proportional, this research found that local autonomy spirit is rarelyBroadcasting Act No. 32/2002 has transformed Radio Republik Indonesia (RRI) and Televisi Republik Indonesia (TVRI) from a state-owned-body to public-broadcasting-service. This research aimed to investigate the impacts experienced by those two organizations concerning their philosophies, role, functions, and its implementation on operational levels. Utilizing case studies in West Java and South Sulawesi (Makasar), it is found that broadcasting dynamics in both area are highly dynamic. On the level of normative, both are consistent enough. But on the level of empirical implementation, there were still many obstacles. Although institutional structure relatively proportional, this research found that local autonomy spirit is rarely